Expression of olfactory signaling genes in the eye. - Alexey Pronin; Konstantin Levay; Dmitry Velmeshev; Mohammad Faghihi; Valery I Shestopalov; Vladlen Z Slepak (PLoS ONE)
Purpose To advance our understanding how the outer eye interacts with its environment, we asked which cellular receptors are expressed in the cornea, focusing on G protein-coupled receptors. Methods Total RNA from the mouse cornea was subjected to next-generation sequencing using the Illumina platform. The data was analyzed with TopHat and CuffLinks software packages. Expression of a representative group of genes detected by RNA-seq was further analyzed by RT-PCR and in situ hybridization using RNAscope technology and fluorescent microscopy. Results We generated more than 46 million pair-end reads from mouse corneal RNA. Bioinformatics analysis revealed that the mouse corneal transcriptome reconstructed from these reads represents over 10,000 gene transcripts. We identified 194 GPCR transcripts, of which 96 were putative olfactory receptors. RT-PCR analysis confirmed the presence of several olfactory receptors and related genes, including olfactory marker protein and the G protein associated with olfaction, Gαolf. In situ hybridization showed that mRNA for olfactory marker protein, Gαolf and possibly some olfactory receptors were found in the corneal epithelial cells. In addition to the corneal epithelium, Gαolf was present in the ganglionic and inner nuclear layers of the retina. One of the olfactory receptors, Olfr558, was present primarily in vessels of the eye co-stained with antibodies against alpha-smooth muscle actin, indicating expression in arterioles. Conclusions Several species of mRNA encoding putative olfactory receptors and related genes are expressed in the mouse cornea and other parts of the eye indicating they may play a role in sensing chemicals in the ocular environment.